2012
DOI: 10.2310/7750.2011.10117
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol in the Treatment of Problematic Infantile Hemangioma: Review of 35 Consecutive Patients from a Vascular Anomalies Clinic

Abstract: Background: Propranolol, a nonselective b-blocker, has been reported as efficient for controlling the growth of complicated infantile hemangiomas (IHs). No uniformly accepted protocol exists regarding the administration of oral propranolol for IH.Objective: We sought to share our experience using propranolol for problematic IH and to evaluate the efficacy of this treatment modality.Methods: A retrospective chart review analysis was performed for 35 consecutive children treated with propranolol as an oral solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…However, because of increased ulceration, pain, and bleeding in the genital location, treatment is recommended. After the introduction of propranolol therapy, its use became widespread, lowering the risk of long-term complications from observation or surgery caused by functional impairment and scarring [10]. In our study, 25% fewer patients in Era 2 experienced ulceration compared with those in the Era 1 (p Z 0.213), likely because of early initiation of propranolol therapy.…”
Section: Discussioncontrasting
confidence: 49%
“…However, because of increased ulceration, pain, and bleeding in the genital location, treatment is recommended. After the introduction of propranolol therapy, its use became widespread, lowering the risk of long-term complications from observation or surgery caused by functional impairment and scarring [10]. In our study, 25% fewer patients in Era 2 experienced ulceration compared with those in the Era 1 (p Z 0.213), likely because of early initiation of propranolol therapy.…”
Section: Discussioncontrasting
confidence: 49%
“…Forty‐three patients (88%) exhibited resolution of symptoms within 24 hours of propranolol administration. This quick response is consistent with the time course documented for improvement in cutaneous hemangiomas, as well as with the existing literature regarding airway hemangiomas …”
Section: Discussionsupporting
confidence: 90%
“…Price et al reported that 82% (56/68) of patients had at least 75% clearance of their IH(s). Talaat et al reported 75% (60/80) of patients with > 75% clearance and 94% (75/80) with >50% clearance of their IH(s). Bertrand et al reported two studies, one with 100% (12/12) of patients with >50% improvement and another with 97% (34/35) of patients with clearance between 25% and 75% with propranolol .…”
Section: Resultsmentioning
confidence: 99%